Shaikh’s theory of inflation: Empirical evidence from european countries (2001–20) - BOLKOL, HAKKI KUTAY (My University, 2023)
Anwar Shaikh has proposed the classical theory of inflation in his recent book Capitalism, Competition, Conflict, Crisis. Even though it is a relevant and well-founded heterodox theory, the empirical literature on the subject is scanty. In this article, we empirically evaluate the explanatory capabilities of Shaikh’s theory of inflation for the case of Europe. We constructed GMM and Fixed Effects models for the panel of 23 European countries over the period 2001–20. The overall results demonstrated that Shaikh’s classical theory of inflation generated empirically successful results in explaining the supply dynamics of European inflation, while it produced no statistically significant effect on the demand dynamics of inflation due to the European inflation level, as expected.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Anwar Shaikh; classical theory of inflation; endogenous money; GMM